1999
DOI: 10.1017/s0890037x0004481x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of MON 12037 on the Growth and Tuber Viability of Purple Nutsedge (Cyperus rotundus)

Abstract: A field study was conducted in 1994 and 1995 to determine the efficacy of MON 12037 on purple nutsedge in a bermudagrass turf. The percentage of bermudagrass infested with purple nutsedge following a single application of MON 12037 decreased from 60 to 30% at 18 g ai/ha and to approximately 20% at 36, 54, and 72 g/ha. Regrowth of purple nutsedge occurred between 28 and 55 d after treatment (DAT) and was greatest at 18 g/ha. A second application of MON 12037 reduced purple nutsedge percent infestation similarly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
21
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 9 publications
2
21
0
Order By: Relevance
“…Halosulfuron applied PRE and POST at 35 to 106 g ai/ha controls yellow nutsedge, reducing regrowth and tuber production (Ackley et al 1996;Blum et al 2000;Earl et al 2004;Ferrell et al 2004;Nelson and Renner 2002;Vencill et al 1995). Halosulfuron applied PRE or POST at 10 to 106 g/ha controls purple nutsedge, reducing regrowth and tuber production (Blum et al 2000;Grichar et al 2003;Molin et al 1999;Rao and Reddy 1999;Vencill et al 1995).…”
mentioning
confidence: 99%
“…Halosulfuron applied PRE and POST at 35 to 106 g ai/ha controls yellow nutsedge, reducing regrowth and tuber production (Ackley et al 1996;Blum et al 2000;Earl et al 2004;Ferrell et al 2004;Nelson and Renner 2002;Vencill et al 1995). Halosulfuron applied PRE or POST at 10 to 106 g/ha controls purple nutsedge, reducing regrowth and tuber production (Blum et al 2000;Grichar et al 2003;Molin et al 1999;Rao and Reddy 1999;Vencill et al 1995).…”
mentioning
confidence: 99%
“…Halosulfuron (Sandea; Gowan Company, Yuma, Ariz.) has been identified as a potential herbicide for use in several cucurbit crops (Batts et al, 2001;Brown and Masiunas, 2002;Haar et al, 2002;Johnson and Mullinix, 2002). Halosulfuron, applied in a number of crops controlled yellow and purple nutsedge (Blum et al, 2000;Derr et al, 1996;Vencill et al, 1995), impeded tuber production (Lowe et al, 2000;Nelson and Renner, 2002;Warren and Coble, 1999), and reduced tuber viability (Molin et al, 1999). Previous studies with cucurbits indicated that certain species and cultivars within a species had greater sensitivities than others (Buker and Stall, 2001;Stall and Majek, 1995;Webster et al, 2003), and application method affected crop injury (Garvey et al, 1997;Mitchem and Monks, 1997).…”
mentioning
confidence: 99%
“…Halosulfuron (Trade name Sandea, Gowan Co., Yuma, Ariz.) has been identifi ed as a potential herbicide for use in several cucurbit crops (Batts et al, 2001;Brown and Masiunas, 2002;Haar et al, 2002;Johnson and Mullinix, 2002;Webster and Culpepper, 2005;Webster et al, 2003) and solaneceous crops (Buker et al, 2004;Grichar et al, 2003;Haar et al, 2002). Halosulfuron controls purple and yellow nutsedge (Blum et al, 2000;Derr et al, 1996;Vencill et al, 1995), impedes tuber production (Lowe et al, 2000;Nelson and Renner, 2002;Warren and Coble, 1999), reduces tuber viability (Molin et al, 1999), prevents shoot regrowth and reduces nutsedge competitiveness . While halosulfuron effectively controls both nutsedge species, crop tolerance limits adoption of this tactic for a broad range of vegetable crops.…”
mentioning
confidence: 99%